2009
DOI: 10.1111/j.1600-0501.2009.01848.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone dimensional variations at implants placed in fresh extraction sockets: a multilevel multivariate analysis

Abstract: Clinicians must consider the thickness of the buccal bony wall in the extraction site and the vertical as well as the horizontal positioning of the implant in the socket, because these factors will influence hard tissue changes during healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
223
2
14

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(268 citation statements)
references
References 20 publications
29
223
2
14
Order By: Relevance
“…83mm versus 0.6 ± 0.55mm. Similarly, Tomasi et al (2010) observed in a multilevel analysis how every 1mm increase of the implant position towards the buccal aspect resulted in a resorption of the buccal bone wall of 0.22mm. observed on CBCTs after 6 months how the buccal plate was preserved when implants were lingually positioned.…”
Section: Implant Positionmentioning
confidence: 99%
See 3 more Smart Citations
“…83mm versus 0.6 ± 0.55mm. Similarly, Tomasi et al (2010) observed in a multilevel analysis how every 1mm increase of the implant position towards the buccal aspect resulted in a resorption of the buccal bone wall of 0.22mm. observed on CBCTs after 6 months how the buccal plate was preserved when implants were lingually positioned.…”
Section: Implant Positionmentioning
confidence: 99%
“…A more palatal placement of the implants in the flapless group could explain the increased lingual height reduction as well as the greater stability of the buccal wall height in this treatment group (Tomasi et al 2010). Blanco et al (2008) compared flap and flapless approach on immediate implants in a beagle dog model and showed that, at three months, the first bone to implant contact was located more apically on those sites were a flap had been raised, but it was not statistically significant.…”
Section: Flap Versus Flapless Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…A clinical study conducted by Evans and Chen [23] showed that implants whose shoulders were placed in the vestibular direction or coincided with a line passing through the cervical margin of the adjacent teeth led to a recession of the vestibular tissue three times higher than implants placed in the lingual direction (1.8 vs 0.6 mm) [23,24].…”
Section: Diagnosis and Implant Placementmentioning
confidence: 99%